Kristus Sebagai Imam Besar: Studi Eksegesis Ibrani 9:11-28 dan Relevansinya Bagi Gereja Bethel Injil Sepenuh Kasih Kristus Tarutung - Christmas Jonathan Simanugkalit; Warseto Freddy Sihombing; Erman Sepniagus Saragih (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research is intended to understand the role of Christ as High Priest and its significance for Christ Tarutung's Christ Full Gospel Bethel Church. A priest had responsibilities regarding the presentation of offerings, and the high priest served as head of the priests. Christ, as the High Priest, served as intercessor for humans and sacrificed his blood and himself to atone for human sins. The pastor in GBIS Love of Christ, as leader, is responsible for guiding and shepherding the congregation. The research method in this scientific work is a qualitative method with a descriptive approach (library research). This research also uses an exegetical approach by analyzing verses and sources related to Hebrews 9:11-28. This method is used by the author to find useful materials according to the research objectives. In this research, we will explore Christ as the High Priest and its relevance for the Full Gospel Bethel Church, the Love of Christ Tarutung congregation. Christ as the High Priest, the role of Christ as the High Priest is the blood of Christ as a sacrifice to redeem human sins, Christ becomes the High Priest who passes through Heaven, Christ as the High Priest grants eternal salvation to all those who wait patiently.